Beyond the U-curve: Citizen preferences on European integration in multidimensional political space. (September 2022) - Toshkov, Dimiter; Krouwel, André
One of the major findings of the literature on Euroscepticism is that support for European integration generally declines as one moves closer to the extremes of the left-right ideological spectrum. However, in multidimensional policy space, Euroscepticism varies in more complex ways. This article explores the relief of Euroscepticism for citizens in four European states – the Netherlands, Germany, Italy and France – based on data from voting advice applications fielded before the 2019 elections of the European Parliament. The results reveal that the way Euroscepticism maps onto other dimensions differs significantly for citizens and for parties and across political contexts. Such variation is important for understanding how preferences for European integration are embedded into existing structures of political competition.